BOOSTING STUDENTS' INTEREST IN ENGLISH SPEAKING LEARNING: DEBATING AND ASSESSING ISSUES - Asriadi Rasyid; Rafi’ah Nur; Ammang Latifa; Rahmatullah Syaripuddin; Suhria (Universitas Muhammadiyah Makassar, 2026)
In the context of globalization, English speaking proficiency has become a crucial skill for academic and professional success. However, many students still demonstrate low interest and engagement in speaking activities due to the lack of interactive and student-centered learning strategies. This study aims to investigate the effectiveness of British Parliamentary Debate and peer assessment in enhancing students’ interest in learning English speaking skills. The novelty of this research lies in the integration of a formal international debate system with collaborative peer-based evaluation to foster both cognitive and affective engagement. Employing a quantitative descriptive design, the study involved 45 third-semester students of the English Department at Universitas Muhammadiyah Parepare. Data were collected through a 32-item Likert-scale questionnaire and analyzed to measure students’ interest across three dimensions: desire, necessity, and happiness. The findings reveal a high level of student interest, with an overall mean score of 88.68, categorized as “strongly interested.” Among the dimensions, urgency (89.47) and desire (93.68) emerged as dominant factors, indicating that students perceived the learning activities as both essential and highly engaging. Additionally, students reported positive emotional responses, including increased confidence and enjoyment in speaking activities. This study contributes to English language teaching by demonstrating that the integration of British Parliamentary Debate and peer assessment creates a dynamic, interactive, and collaborative learning environment that significantly enhances students’ motivation and speaking engagement. It is recommended that these strategies be more widely implemented to improve both affective and communicative competencies in EFL classrooms